Base-Promoted Reaction between N-Acyl Benzotriazoles and p-Toluenesulfonylmethyl Isocyanide (TosMIC): A Facile Synthesis of 4,5-Disubstituted Oxazoles - You, Hui; Liu, Daming; Pan, Mengni; Shen, Yue; Li, Yang; Li, Wanfang (Synlett, 2024)
We herein developed a base-promoted cyclization reaction between N-acyl benzotriazoles and p-toluenesulfonylmethyl isocyanide (TosMIC) to afford 4,5-disubstituted oxazoles. In the presence of 3 equiv of K3PO4, the two readily available starting materials reacted in N,N-dimethylformamide at 80 °C to give 28 examples of 4-tosyl-5-aryl, -alkyl, or -alkenyl-substituted oxazoles in moderate to high yields.
Keywords: oxazole synthesis; N-acyl benzotriazole; p-toluenesulfonylmethyl isocyanide